Modelling of Virtual Synchronous Converter for Grid-inverter Synchronization in Microgrids Applications - Md. Ruhul Amin; Shamsul Aizam Zulkifli (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
In this paper, virtual synchronous converter (VSCon) is modelled which behaves as synchronous generator including its all real-time characteristics in operating inverter. This VSCon is used to synchronize grid and inverter while integrating distributed generated power to microgrids. The frequency and voltage synchronization can be controlled by using synchronous generator mathematical model is installed into the inverter. The whole unit of VSCon operated is simulated in Matlab/Simulink for observing all consequences for synchronizing voltage, frequency and phase-angle. It is verified that the next generation energy resources can be integrated into microgrid making synchronization grid-inverter using VSCon. The simulation results are given to verify the concept of modelling VSCon functioning inverter as a synchronous generator.